Development of a new indicator of functional reliability and its evaluation using multivariable polynomial regression - Барабаш, Олег Віталійович; Макарчук, Андрій (Київський національний університет імені Тараса Шевченка, 2024)
B a c k g r o u n d . Functional The functional stability of distributed systems is becoming increasingly significant with the advancement of information technologies. Consequently, the formalization of this concept has gained relevance. Mathematical formalization of functional stability in the form of its indicators and criteria has been underway for several decades. Functional stability indicators play a key role in this process, and many such indicators have already been formulated. However, a major drawback of most of these indicators is that they are not only computationally complex but also dependent on numerous other parameters, or they fail to comprehensively describe the functional stability of the distributed system in question. In this paper, a new functional stability indicator is introduced that avoids the second of these drawbacks. The first drawback is addressed through the use of an estimation method based on multivariate polynomial regression. M e t h o d s . The study utilized methods of computer modeling and approximation techniques. R e s u l t s . A modification of an existing indicator, known in the literature as the probability of reliability, was chosen as the method for developing the new functional stability indicator. By making certain assumptions and applying transformations, a measure was obtained that possesses certain desirable properties, namely: this measure lies strictly within the interval from zero to one, and the larger it is, the more functionally stable the distributed system under consideration can be deemed. However, the resulting functional stability indicator requires extensive calculations, prompting an attempt to estimate this indicator using approximation methods. This study explored the potential of applying multivariate polynomial regression. According to computer modeling, to achieve an average accuracy of two percent, it is sufficient to use a five-dimensional polynomial regression of the fourth degree. Increasing the degree of the five-dimensional regression model beyond this does not result in significant error reduction. C o n c l u s i o n s . The functional stability indicator introduced in this study provides a convenient means for investigating the functional stability of distributed systems. However, it demands a significant amount of computation. For this reason, a method for estimating the introduced functional stability indicator has been presented, which allows for relatively accurate computation of this indicator.

В с т у п . Функціональна стійкість розподілених систем стає все важливішим поняттям із розвитком інформаційних технологій. Набуває актуальності певна формалізація цього поняття. Математична формалізація функціональної стійкості у вигляді її показників і критеріїв відбувається вже не перше десятиліття. Особливу роль тут відіграють саме показники функціональної стійкості, яких сформульовано вже не так і мало. Однак головним недоліком більшості з них є те, що окрім своєї високої обчислювальної складності, ці показники ще й залежать від багатьох інших параметрів, або те, що вони недостатньо повно описують функціональну стійкість розглядуваної розподіленої системи. В цій роботі введено новий показник функціональної стійкості, у якого відсутній другий із згаданих недоліків. Перший недолік усувають завдяки використанню оцінювання, основаного на багатовимірній поліноміальній регресії. М е т о д и . Використано методи комп’ютерного моделювання та наближення. Р е з у л ь т а т и . Як спосіб розроблення нового показника функціональної стійкості вибрано модифікацію існуючого показника, відомого в літературі як імовірність справності. Висунувши певні припущення та провівши деякі перетворення, отримано величину, яка має певні хороші властивості, а саме: вказана величина міститься строго в проміжку від нуля до одиниці, а також чим більшою вона є, тим більш функціонально стійкою можна вважати розглядувану розподілену систему. Проте отриманий показник функціональної стійкості вимагає дуже багато обчислень, тому здійснено спробу побудови оцінки цього показника за допомогою методів наближення. В межах указаного дослідження було вивчено можливості застосування багатовимірної поліноміальної регресії. Як показало комп’ютерне моделювання, для досягнення точності, рівної, в середньому, двом відсоткам, достатньо використовувати п’ятивимірну поліноміальну регресію четвертого степеня. Подальше підвищення степеня п’ятивимірної регресійної моделі не даватиме значущого зменшення похибки. В и с н о в к и . Введений у роботі показник функціональної стійкості є зручним засобом для дослідження функціональної стійкості розподілених систем. Однак він вимагає значної кількості обчислень. Із цією метою представлено метод оцінювання вказаного показника, який дозволяє достатньо точно обчислити введений показник функціональної стійкості.
Розроблення нового показника функціональної стійкості та його оцінювання за допомогою багатовимірної поліноміальної регресії
Keywords: functional stability; indicator; approximation; optimization; regression; multivariable functions.; функціональна стійкість; показник; наближення; оптимізація; регресія; функції багатьох змінних.